2023
DOI: 10.1186/s13023-023-02786-3
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the phenotypes and genotypes of facial infiltrating lipomatosis associated with PIK3CA mutations

Abstract: Background Facial infiltrating lipomatosis (FIL) is a rare congenital disorder characterized by unilateral facial swelling, for which surgery is the prevailing therapeutic option. Several studies have shown that the development of FIL is closely associated with PIK3CA mutations. This study aimed to further identify rare clinical features and underlying molecular variants in patients with FIL. Results Eighteen patients were included in this study, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Twenty-one patients underwent genetic testing, with the genotypes of 18 patients previously described in our prior investigation [ 13 ]. The remaining three patients carried PIK3CA p.Asn345Lys, p.Cys420Arg, and p.Glu453Lys mutations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one patients underwent genetic testing, with the genotypes of 18 patients previously described in our prior investigation [ 13 ]. The remaining three patients carried PIK3CA p.Asn345Lys, p.Cys420Arg, and p.Glu453Lys mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen specimens were found to harbor somatic PIK3CA mutations. Furthermore, our previous analysis [ 13 ], revealed that hotspot mutations were associated with more severe FIL phenotypes, further enriching our understanding of FIL's molecular pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Histologically, it is marked by mature, non-encapsulated adipocytes that can diffusely infiltrate the adjacent soft tissues [ 1 ]. The condition is visible at birth, with patients exhibiting hemifacial swelling and myriad phenotypic features such as macrodontia, hemimacroglossia, lip hypertrophy, epidermal nevi, and mucosal neuromas [ 2 ]. These abnormalities can significantly impact facial appearance.…”
Section: Introductionmentioning
confidence: 99%
“…PIK3CA variants can result in a structural alteration in p110α, leading to its release from the inhibitory effects of the p85α regulatory subunit, thereby continuously stimulating downstream signaling molecules and causing overactivation of the PI3K-AKT-mTOR pathway [ 9 ]. Our previous work found that PIK3CA hotspot variants (E542K, E545K, H1047R) can lead to more severe FIL phenotypes, characterized by an increased number and severity of affected soft tissues [ 2 ]. However, although PIK3CA variants may be the primary cause of FIL, it is still unclear how they initiate these pathological processes by impacting downstream molecules.…”
Section: Introductionmentioning
confidence: 99%